2017
DOI: 10.24200/imminv.v2i3.47
|View full text |Cite
|
Sign up to set email alerts
|

Survey On Methanol Poisoning Epidemic in Rafsanjan City in Year 2013

Abstract: Background: Examination and early detection of the methanol toxicity epidemic are very important, so identification and initiation of appropriate therapy can significantly reduce morbidity and mortality. Therefore, this study was aimed to investigation methanol poisoning epidemic in Rafsanjan city. Methods: This case series study was conducted in 252 patients with methanol poisoning in 2013 in the Ali-ibn-Abi-Talib hospital of Rafsanjan. Data were through interviews and records that were collected at hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…As per Mostafazadeh and Eghbali, 14.3% of patients encountered visual complications at discharge [7]. Mirzaei et al reported a prevalence of 39.7% for vision problems, i.e., mentioned as the most common complication [8]. However, in the study by Massoumi et al, 71% of the examined patients manifested nausea and vomiting.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As per Mostafazadeh and Eghbali, 14.3% of patients encountered visual complications at discharge [7]. Mirzaei et al reported a prevalence of 39.7% for vision problems, i.e., mentioned as the most common complication [8]. However, in the study by Massoumi et al, 71% of the examined patients manifested nausea and vomiting.…”
Section: Discussionmentioning
confidence: 98%
“…Most patients with methanol poisoning manifest some clinical signs of ophthalmological abnormalities, even in the absence of visual dysfunction [5]. The prevalence of visual disturbances after methanol poisoning ranges from 29% to 64% [1,2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%